Cervical Cancer in Ethiopia: The Effect of Adherence to Radiotherapy on Survival. (23rd March 2018) - Moelle, Ulrike; Mathewos, Assefa; Aynalem, Abreha; Wondemagegnehu, Tigeneh; Yonas, Bekuretsion; Begoihn, Matthias; Addissie, Adamu; Unverzagt, Susanne; Jemal, Ahmedin; Thomssen, Christoph; Vordermark, Dirk; Kantelhardt, Eva J.
Abstract: Background: Discontinuation of radiotherapy (RT) for cervical cancer (CC) in sub‐Saharan Africa is common because of patient‐ and health service‐related reasons. This analysis describes toxicities and the effect of adherence on survival. Materials and Methods: A total of 788 patients with CC (2008–2012) who received RT at Addis Ababa University Hospital were included. External beam RT without brachytherapy was performed according to local guidelines. We previously described survival and prognostic factors. Now we analyzed adherence and survival according to total doses received. Adjustment via multivariate cox regression analysis was done. Results: One‐year overall survival (OS) after radical RT ( n = 180) for International Federation of Gynecology and Obstetrics (FIGO) stages IIA–IIIA was 89% for discontinuation (<72 Gy) and 96% for adherence (≥72 Gy; hazard ratio [HR], 1.3; 95% confidence interval [CI], 0.5–3.3). One‐year OS after nonradical RT ( n = 389) for FIGO stages IIIB–IVA was 71% for discontinuation (<40 Gy) and 87% for adherence (44–50 Gy; HR, 3.1; 95% CI, 1.4–6.9). One‐year OS for FIGO stages IIIB–IVB ( n = 219) after one compared with two or more palliative single fractions of 10 Gy were 14% and 73% respectively (HR, 7.3; 95% CI, 3.3–16). Reasons for discontinuation were toxicities, economic background, and RT machine breakdown. Grade 1–2 late toxicities were common (e.g., 30% proctitis, 22% incontinence). Grade 3 early and late toxicities were seen in 5% and 10% respectively; no grade 4 toxicities occurred. Conclusion: Patients who adhered to guideline‐conforming RT had optimum survival. Better supportive care, brachytherapy to reduce toxicities, socioeconomic support, and additional radiation capacities could contribute to better adherence and survival. Implications for Practice: This study presents the effect of adherence on survival of 788 patients with cervical cancer receiving external beam radiotherapy without brachytherapy in Ethiopia. Discontinuation of planned radiotherapy according to local guidelines considerably reduced survival for all International Federation of Gynecology and Obstetrics (FIGO) stages treated (hazard ratios were 1.3, 3.1, and 7.3 for FIGO stages IIA–IIIA and IIIB–IVA and the palliative approach, respectively). Early toxicity (5% grade 3) should be treated to improve adherence. Economic difficulties and machine breakdown should also be addressed to reduce discontinuation and improve survival. Abstract : This article assesses the current practice of radiotherapy for cancer of the uterine cervix. The outcomes of patients who adhered to radiotherapy guidelines were compared with patients who discontinued radiotherapy, and conclusions were drawn about whether and to what extent patients benefited from adherence.